A Case of Chemotherapy-Refractory “THRLBCL like Transformation of NLPHL” Successfully Treated with Lenalidomide - Mamatha Siricilla; Lydia Irwin; Andres Ferber (Case Reports in Oncological Medicine)
Nodular lymphocyte predominant Hodgkin lymphoma (NLPHL) is a subtype of nonclassical Hodgkin lymphoma (HL). It resembles non-Hodgkin lymphoma (NHL), by expressing classic B cell markers such as CD20 and CD79a however lacks definitive HL markers (such as CD15 and CD30). T cell histiocyte-rich large B cell lymphoma (THRLBCL), on the other hand, is a distinct entity classified under NHL and considered a variant of diffuse large B cell lymphoma (DLBCL). NLPHL can look morphologically and immunologically similar to THRLBCL and often poses a diagnostic challenge. Neoplastic cells in both NLPHL and THRLBCL express B cell markers and are typically scattered in a background of reactive cells. The two major differences are the background cell type and the morphologic pattern. Despite having a phenotypic resemblance, they have distinct biologic behavior and clinical course. NLPHL typically has an indolent course, and THRLBCL has an aggressive course. Hence, differentiating these two entities is critical not only for prognosis but for treatment purposes. Of note, NLPHL has a small risk of transformation to an aggressive lymphoma such as THRLBCL.